2016
DOI: 10.1017/s1049023x16001230
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pediatric Education for Emergency Medical Services Providers: A Qualitative Study

Abstract: Focus groups identified four themes surrounding preparation of EMS personnel for providing care to pediatric patients. These themes can guide future educational interventions for EMS to improve pediatric prehospital care. Brown SA , Hayden TC , Randell KA , Rappaport L , Stevenson MD , Kim IK . Improving pediatric education for Emergency Medical Services providers: a qualitative study. Prehosp Disaster Med. 2017;32(1):20-26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A general discomfort in treating children, especially critically-ill children, was a recurring theme in the IDIs. That discomfort and the need for pediatric-specific EMS education have been reported over the past thirty years [18][19][20][21][22]. The IDIs revealed that despite those repeated calls for prehospital pediatric education, current educational practices are still not alleviating EMS clinicians' widespread discomfort in caring for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general discomfort in treating children, especially critically-ill children, was a recurring theme in the IDIs. That discomfort and the need for pediatric-specific EMS education have been reported over the past thirty years [18][19][20][21][22]. The IDIs revealed that despite those repeated calls for prehospital pediatric education, current educational practices are still not alleviating EMS clinicians' widespread discomfort in caring for children.…”
Section: Discussionmentioning
confidence: 99%
“…EMS clinicians have historically reported discomfort with treating pediatric patients [18][19][20][21]. Previous studies have found infrequent exposure to pediatric patients and limited pediatric-specific formal education lie at the heart of that discomfort [18][19][20]22,23]. Additionally, there is even less exposure to critically ill children and in performing advanced life support (ALS) skills and procedures [19].…”
Section: Introductionmentioning
confidence: 99%
“…( 2 ) Yet EMS providers are an essential link in the chain of survival, and when needed, these pediatric skills must be executed effectively. Given limited clinical exposure, EMS providers cannot rely on experience alone to maintain proficiency in pediatric assessment and resuscitation skills and need access to effective continuing education opportunities ( 3 , 4 ). Simulation has been demonstrated as an effective tool within medical education, including training for low frequency, high stakes events ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, simulation education can be resource intensive and costly. EMS providers face additional challenges when accessing pediatric simulation including lack of standardization in pediatric continuing education requirements, and limited access to subject matter experts and simulation resources ( 3 ). Research on the most effective means of pediatric continuing education for EMS providers is limited ( 3 , 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…24 Qualitative studies of EMS providers reveal education, training, and practical barriers (e.g., low frequency of encounters compared to adults, difficulty obtaining IV access, drawing up weight-based medication doses, communicating with parents, emotional difficulty in treating ill children) to pediatric EMS care. [25][26][27] Therefore, in addition to evaluating clinical outcomes, EMS studies (particularly pediatric EMS studies), must systematically evaluate how best to implement evidence-based practices in the unique prehospital setting. This trial employs a hybrid effectiveness-implementation design to determine if EMS-administered OCS improves clinical outcomes for pediatric asthma, the cost of EMS OCS administration, how EMS transport time affects clinical and economic outcomes, and implementation considerations.…”
Section: Introductionmentioning
confidence: 99%